Socialization of Social Media Job Scams and Human Trafficking Case Reporting Procedures in Indramayu District - Pratamawaty, Benazir Bona; Dewi, Evie Ariadne Shinta; Limilia, Putri (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
Indramayu district is one of the migrant enclaves in West Java province, which continuously faces an increased number of human trafficking cases year by year. The modus and means of human trafficking victims recruitment were used to target subdistrict areas people by person to person, now shifted to the optimization of the internet. The traffickers attempt to lure victims through social media by posting job vacancy advertisements which offer a high salary. Unfortunately, society lacks information or knowledge about differentiating a legitimate job offer from a human trafficking lure. In addition, society also lacks information on the procedures and the required documents to submit a police report on a possible human trafficking case. The community service titled “Identify then Report” aims to introduce and disseminate various modus and means of human trafficking practice, to educate on how to identify human trafficking modus in social media and to inform the procedure and required documents to submit a police report on a possible human trafficking case. The community service was held in one of the migrant enclaves in Indramayu district, Kenanga town, located in the headquarters office of the Indonesian Migrant Family Organization (KAMI) and attended by 34 participants. The community service speakers delivered materials regarding the various modus and means of human trafficking recruitment and socialized how to identify human trafficking recruitment modus on social media. In addition, the speakers explained the procedures and required documents for submitting a police report on a possible human trafficking case to the participants.